The Impact of Service Quality on Student Behavioral Intentions in Higher Education - Petrovicova, Vladimir; Vladimir, Marianna (Journal of Policy Options, 2021)
The paper focuses on the measurement of service quality in higher education and emphasizes the importance of developing psychometrically robust and contextually appropriate measurement instruments. The study builds on the SERVQUAL scale, a widely validated tool used across various service industries. Although the SERVQUAL model originally comprises five dimensions of service quality, the research reveals a six-dimensional structure for assessing service quality in higher education. This finding suggests that while there are notable similarities to the SERVQUAL framework, additional dimensions are necessary to capture the unique aspects of service quality in the context of higher education. The study conducted with Engineering Management students highlights a consistent shortfall between students' perceptions and their expectations across all service quality determinants. The most pronounced gap was observed in the area of potential for future career development. This dimension, despite being the area with the largest negative discrepancy, is identified as the most significant predictor of students' future behavioral intentions. The research emphasizes the need for addressing this critical aspect to align service quality with students' expectations. The paper also offers managerial implications and suggests directions for future research to better understand and improve service quality in higher education.